Effects of the principal stress rotation in numerical simulations of geotechnical laboratory cyclic tests. (May 2019) - Wang, Zhe; Yang, Yunming; Lu, Nan; Li, Yao; Yu, Hai-Sui
Abstract: Cyclic stress paths in geotechnical experiments can generate considerable principal stress rotation (PSR) in the saturated soil. The PSR without changes of principal stress magnitudes can generate additional excess pore water pressures and plastic strains, thus accelerating liquefactions in undrained conditions. This paper simulates a series of laboratory tests considering the PSR using two types of sand. The impact of PSR is taken into account by using an elastoplastic soil model developed on the basis of a kinematic hardening soil model with the bounding surface concept. The soil model considers the PSR by treating the stress rate generating the PSR independently. The capability of this soil model is verified by comparing the numerical predictions with and without PSR, as well as experimental results. The comparative results indicate that the simulation with the soil model considering the PSR can better reproduce the test results on the development of shear strain, reduction of effective confining pressure and liquefaction than the soil model without PSR. Therefore, it is important to consider PSR effects in simulations of geotechnical experiments under cyclic loadings.